RARE-37. OCCURRENCE OF GLIOMA IN PREGNANT PATIENTS: INSTITUTIONAL CASE SERIES AND REVIEW OF THE LITERATURE. (5th November 2018) - Singh, Pawan; Pan, Edward; Sewell, Josie; Hatanpaa, Kimmo
Abstract: BACKGROUND: The treatment of glioma in pregnant patients has limited data in the literature. There are no guidelines in place currently for this population. Another controversial topic is the use of gadolinium contrast in pregnant patients. This retrospective institutional case review series looks at the extent of resection, grade of tumor, use of contrast and outcome. This case series is the first to document IDH-mutation and MGMT methylation status either by immuno-histological stain or by genetic sequencing. METHODS: 5 patient cases were reviewed by retrospective search with diagnosis of glioma and pregnancy. 4 patients were diagnosed with glioma during pregnancy; 1 patients were diagnosed with glioma prior to pregnancy. 3 patients were monitored with contrasted MRIs after 2 nd trimester, there were no adverse effects to the fetus. Only 1 patient developed progression during course of chemotherapy, the remaining 4 patients remained progression free after completion of chemotherapy. RESULTS: This case series documented that 3 of 5 patients had IDH-mutated gliomas; 1 of 3 glioblastomas (GBM) were MGMT methylated. 3 of 5 patients achieved gross total resection. All intracranial neoplasms were of astrocytic lineage: 3 GBMs, 1 anaplastic astrocytoma and 1 diffuse astrocytoma. All patients delivered healthy infants. 4 patients continue to be progression free since completion of chemotherapy with 1 patient experiencing progression during course of chemotherapy. Median progression free survival was 20 months, all patients are alive at time of publication. CONCLUSION: This case series highlights how individualized care through a multi-disciplinary approach can result in favorable outcomes in this patient population.